ДІЯЛЬНІСТЬ ЧЛЕНІВ НТШ У СТВОРЕННІ ТА ДІЯЛЬНОСТІ УКРАЇНСЬКОГО УНІВЕРСИТЕТУ (Zaporizhzhia Historical Review, 2021)
The article showss many-sided labour of research workers of the scientific society after Shevchenko in the creation of the own high school, representation of national science and education.